2020
DOI: 10.21203/rs.3.rs-52929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV Prevalence Trends and Disparities by Gender and Urban-rural Residence Among Adolescents in Sub-saharan Africa

Abstract: Background In sub-Saharan Africa HIV transmission is a major challenge in adolescents, especially among girls and those living in urban settings. Major international efforts have aimed at reducing sexual transmission. This analysis aims to assess the trends in HIV prevalence by gender in adolescents, as well as urban-rural disparities. Methods HIV prevalence data were obtained for 30 countries with a national survey since 2010 and for 23 countries with one survey circa 2005 and a recent survey circa 2015. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 However, a recent review of HIV trends across 25 sub-Saharan African countries showed a promising downward trend in HIV prevalence among both male and female adolescents. 2 The study also found a difference in HIV prevalence based on population density, with adolescents residing in urban areas having at least 1.5 times higher HIV prevalence than counterparts residing in rural areas. 2 All in all, given that Africa is the only continent where the youth population continues to rise and accounts for the majority of new HIV cases, prioritizing adolescents in the HIV response in sub-Saharan Africa is of the utmost importance.…”
Section: Introductionmentioning
confidence: 67%
“…1 However, a recent review of HIV trends across 25 sub-Saharan African countries showed a promising downward trend in HIV prevalence among both male and female adolescents. 2 The study also found a difference in HIV prevalence based on population density, with adolescents residing in urban areas having at least 1.5 times higher HIV prevalence than counterparts residing in rural areas. 2 All in all, given that Africa is the only continent where the youth population continues to rise and accounts for the majority of new HIV cases, prioritizing adolescents in the HIV response in sub-Saharan Africa is of the utmost importance.…”
Section: Introductionmentioning
confidence: 67%